Instrumental and Political Explanations in the Implementation of Various Prison Public-Private Partnership (PPP) Models - Aisyah, Sani Siti; Meliala, Adrianus; Sulhin, Iqrak (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
This study highlights that the practice of Public-Private Partnership (PPP) in prison, based on the experiences of various countries such as the United States, England, Australia, France, Japan, and Canada, does not have a single pattern. The diversity of PPP practice patterns in prison is identified by this study in various prison PPP models consisting of: 1) the "private governance" model; 2) the "hybrid management" model; 3) the "service infrastructure" model; and 4) the "contracting out certain limited functions" model. Through a literature study combined with an analysis of policy design theory, this study explains that the diversity of prison PPP models is based on a diverse implementation process in which there are various considerations for the implementation of each model. The various considerations for the implementation of those models are generally grouped into instrumental and political explanations. The implementation of the "private governance" model is a political and administrative decision. The implementation of the "hybrid management" and "service infrastructure" models are administrative decisions with political support. The implementation of the "contracting out certain limited functions" model is an administrative decision.